PENGARUH GREEN BANKING TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA (PERIODE TAHUN 2018-2022) - Mahardika, Putu Arya Diva; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2023)
Environmental problems include climate change, and an increase in the frequency of natural disasters have become widespread phenomena. These harmful trends have been aided by the absence of environmental considerations in banking operations. The idea of "Green Banking" aims to lower carbon emissions both inside and outside of banks. This research aims to analyze the impact of implementing Green Banking on the profitability of banks listed on the Indonesia Stock Exchange during the period 2018-2022. Green Banking is measured using the Green Banking Disclosure Index (GBDI), along with M-Banking Transaction Frequency, Bank Efficiency, and CSR Funds as independent variables. Profitability is projected through the Return on Assets (ROA) as the dependent variable. This research found that partially, CSR funds have a positive and significant influence on ROA (Return on Assets). However, factors like GBDI, M-Banking transaction frequency, and bank efficiency have a negative and significant influence on ROA. Tested simultaneously, the implementation of green banking, including GBDI, M-Banking transaction frequency, bank efficiency, and CSR funds, has a positive and significant effect on profitability.